Efecto de una Intervención en Teoría de la Mente en un Grupo de Adolescentes con Edades Comprendidas entre los 16 a los 21 Años con Trastorno del Espectro Autista Grado 1 en Medellín - Arango Torres, Mary Elizabeth (Corporación Universitaria Minuto de Dios – UNIMINUTO, 2025)
Las dificultades en la comprensión de los estados mentales ajenos representan uno de los principales desafíos en el desarrollo social y comunicativo de las personas con Trastorno del Espectro Autista (TEA). La atención terapéutica a esta población enfrenta limitaciones en el acceso a programas especializados que promuevan la cognición social y la empatía. El presente estudio se interesó en examinar el efecto de una intervención basada en la Teoría de la Mente (ToM) en un grupo de adolescentes con TEA grado 1 con edades comprendidas entre los 16 y 21 años de Medellín, fundamentándose en los aportes de Baron-Cohen, Frith, Happé y Riviére, quienes destacan la importancia del desarrollo de la cognición social y la comprensión de los estados mentales ajenos en personas con TEA.

Abstract Difficulties in understanding the mental states of others represent one of the main challenges in the social and communicative development of individuals with Autism Spectrum Disorder (ASD). Therapeutic care for this population faces limitations in access to specialized programs that promote social cognition and empathy. The present study aimed to examine the effect of an intervention based on Theory of Mind (ToM) in a group of adolescents with ASD level 1, aged between 16 and 21 years, from Medellín, Colombia. This research was grounded in the theoretical contributions of Baron-Cohen, Frith, Happé, and Riviére, who emphasize the importance of developing social cognition and understanding others’ mental states in individuals with ASD. The study followed a quantitative pre-experimental approach, employing a pretest–posttest design without a control group, with five adolescents selected through purposive sampling. For the assessment, Baron-Cohen’s Reading the Mind in the Eyes Test (2001) and the Sally and Anne Test (Premack & Woodruff, 1978) were used to measure the participants’ ability to infer emotions, intentions, and beliefs. The intervention consisted of a series of structured sessions aimed at strengthening the cognitive and social skills related to Theory of Mind. The results showed significant improvements in emotional and cognitive inference skills, demonstrating that processes associated with Theory of Mind can be stimulated through structured strategies adapted to the cognitive functioning level of adolescents with ASD level 1. Consequently, it is concluded that the intervention promotes the development of cognitive empathy, emotional understanding, and social interpretation skills.
Determinar el efecto de una intervención en Teoría de la Mente en dimensiones específicas como la inferencial emocional, identificación de emociones y el reconocimiento de estados mentales en un grupo de adolescentes con edades comprendidas entre los 16 a 21 años con Trastorno del Espectro Autista grado 1 en Medellín
Keywords: Teoría de la mente; Trastorno del espectro autista; Cognición social